MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Araújo Filho, Luiz Paulo da Silva; Athié, Ivan (LexCult: revista eletrônica de direito e humanidades; v. 3 n. 3 (2019): Edição Comemorativa 2 AnosDO - 10.30749/2594-8261.v3n3p12-13, 2019)
Mensagem dos Dirigentes do TRF2 - biênio 2019/2021.